Feeding dynamics of Terebralia palustris (Gastropoda: Potamididae) from a subtropical mangrove ecosystem. (2nd October 2017) - Raw, Jacqueline L.; Perissinotto, Renzo; Miranda, Nelson A. F.; Peer, Nasreen
ABSTRACT: Mangrove gastropods are largely recognised for their roles as benthic deposit feeders that consume macrophyte-derived detritus. However, microalgae may also make a significant contribution towards the diet of these snails. Here we provide the first report on the rates at which microphytobenthos (MPB) is consumed by Terebralia palustris, an Indo-Pacific mangrove gastropod. Although juvenile T. palustris are generally detritivorous, there is increasing evidence that their occurrence on the seaward edge of the mangrove habitat allows them to incorporate a more nutritious food source to their diets in the form of microalgae. Using an experimental approach that incorporated fluorometric techniques, we found that the feeding activity of T. palustris on MPB was not clearly related to diel and tidal cycles at the subtropical location of Kosi Bay, South Africa during two sampling occasions in February and July 2015. However, a faster ingestion rate and higher consumption/digestion efficiency were recorded during experiments carried out in July. On this sampling occasion a higher percentage consumption of the available MPB was recorded, which corresponded to a lower per-capita availability in this resource. As T. palustris is able to consume MPB at variable rates, the impact of this species on benthic primary productivity within Indo-Pacific mangroves should not be overlooked when considering its integral ecological role within these threatened habitats.